A G-Bond Development: Gamification Media to Improve Literacy, Visualization, and Numeracy in Chemical Bond Learning in High School - Dwiningsih, Kusumawati; Lutfi, Achmad; Hidayah , Rusly; Sukarmin, Sukarmin; Andriani , Novia; Fathoni , Rizal (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study aims to develop and evaluate G-Bond, a gamification-based learning media designed to improve students' literacy, visualisation, and numeracy skills in learning chemical bonds. Methods: The research uses a Research and Development (R&D) approach with a 4D (Define, Design, Develop, Disseminate) model, limited to the development stage. A total of 35 high school students in Gresik Regency participated in the pretest-posttest design of one group. Five experts carry out validation through content assessment, design, and visualisation. Practicality was tested through a student questionnaire, and effectiveness was measured using an N-Gain score. Results: The G-Bond application obtained a perfect validity score (average = 5), was rated very practical (95.14%), and showed moderate to high effectiveness in improving literacy (N-Gain = 0.34), numeracy (0.34), and visualisation (0.74). The most significant improvement occurs in the visualisation aspect. Novelty: G-Bond is the first gamification medium to simultaneously integrate three main skills in one interactive platform based on the topic of chemical bonding. Unlike previous media that focused only on a single aspect or were less connected to the curriculum, G-Bond presents relevant and adaptive game-based contextual challenges for both online and offline learning. Future integration with Augmented Reality (AR) and AI technologies is proposed to enhance immersive and personalised learning experiences.